Main determinants in Mexico's monetary policy decisions: An econometric analysis - Téllez León, Isela Elizabeth; Venegas Martínez, Francisco (Estudios Económicos de El Colegio de México, 2013)
This paper identifies the determinants that affect the probability of deviations from the target interest rate (overnight interbank rate) of Bank of Mexico, through the development of several binary probit models. Among, the determinants of monetary policy decisions of Bank of Mexico several macroeconomic variables are identified in Mexico and the United States and, particularly, some nodes of the Treasury Certificates yield curve. The combination of these variables provides an adequate specification based on standard information criteria from econometric analysis.